The Test and Launch Control Technology for Launch Vehicles - Song, Zhengyu (Springer Singapore, 2018)
This book presents technologies and solutions related to the test and launch control of rockets and other vehicles, and offers the first comprehensive and systematic introduction to the contributions of the Chinese Long March (Chang Zheng in Chinese, or abbreviated as CZ) rockets in this field. Moreover, it discusses the role of this technology in responsive, reliable, and economical access to space, which is essential for the competitiveness of rockets. The need for rapid development of the aerospace industry for both governmental and commercial projects is addressed. This book is a valuable reference resource for practitioners, and many examples and resources are included, not only from Chinese rockets but also from many other vehicles. It covers guidelines, technologies, and solutions on testing and launch control before rocket takeoff, covering equipment-level testing, system-level testing, simulation tests, etc. .